ANALISIS POTENSI PRODUKSI BENIH, PENANGANAN DAN KARAKTERISTIK PERTUMBUHAN BIBIT KEPUH (Sterculia foetida Linn.) SEBAGAI SALAH SATU SUMBER BIOFUEL - , Nurhasybi, Prof. Dr. Ir. Mohammad Naâiem, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Kepuh (Sterculia foetida Linn.) is a potential tree species to be developed as renewable energy resource because of fast growing species that covers large area, its seed contains quite high oil that is considered to be appropriate for biodiesel raw material. The objective of this research is to find out the potential seed production, oil content in seed from several population, seed handling and growing seedling character. Seed collection and field survey on potential seed production was conducted in six areas including Kupang, Mataram, Bali, Tuban, Cirebon, dan Bogor. The prediction of potential seed production was approached by seed production in individual tree. Fruit and seed morphology from different areas was correlated with rainfall and altitude. Biochemical test and oil contain in seed was conducted in every location of seed collection. The seed handling including determination of seed maturation, seed drying, seed storage and seed germination. Criterion of seedling quality for planting was approached through seedling growth character. The results indicated that fruit and seed morphology was significantly different among seed sources but was not significantly correlated with rainfall and altitude of the seed collection areas. The seed sources in dry areas (Bali and Nusa Tenggara) tend to have higher oil content. Model of potential seed production was Pb = -8733,311 + 195,602Tp + 13,339Dp + 673,658Lb, RÂ² = 0,563, remarks : Pb = seed production (grains), Tp = tree height (m), Dp = stem diameter (cm), and Lb = tree crown size (m). The physiological maturity of seed was determined by fruit color from green reddish to red and the seedcoat color from dark brown to black. Kepuh seed was cathegorized as intermediate seed. The seed can be dried until 10 % in moisture content and can be stored for 4 months in dry cold storage (DCS) room, Air Conditioned room and ambient room. Pre-treatment before seed sowing can be conducted by soaking the seed in concentrated H2SO4 for 10 minutes. The root length and seedling sturdiness quotient as much as 7 (seven) was an important factor of kepuh seedling for planting in the field. The best seedling criterion for planting was the initial height more than 40 cm and diameter more than 4 mm.